2022
DOI: 10.1155/2022/1801717
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Prognoses of Breast-Conserving Surgeries for Differently Aged Women with Early Stage Breast Cancer: Use of a Propensity Score Method

Abstract: Background. To explore the effect of age on the prognosis of patients with early stage breast cancer after breast-conserving surgery (BCS) and to provide references for young patients. Methods. All clinical data of patients with early breast cancer undergoing BCS who were treated at Shengjing Hospital of China Medical University from January 2011 to May 2016 were obtained. The primary endpoints were local recurrence (LR) and distant recurrence, and the secondary endpoint was breast cancer-specific survival (BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Of the other evaluated studies, 10 found no difference in the OS, between BCS and mastectomy [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 49 ] while one noted an improved disease free survival and OS with BCS [ 48 ]. A local recurrence, however, was noted to be greater in patients undergoing BCS in two studies [ 44 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the other evaluated studies, 10 found no difference in the OS, between BCS and mastectomy [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 49 ] while one noted an improved disease free survival and OS with BCS [ 48 ]. A local recurrence, however, was noted to be greater in patients undergoing BCS in two studies [ 44 , 49 ].…”
Section: Resultsmentioning
confidence: 99%